Hipnoterapi Untuk Meningkatkan Suport Keluarga Terhadap Pasien Palliative Care (Penyakit Kanker) - Sukur, Andreas Woitila; Higgi, Edwin (Jurnal Keperawatan Muhammadiyah, 2019)
Cancer is one of the leading causes of death throughout the world. In 2012, cancer was the cause of death of around 8.2 million people. Cancer is very influential on the development of psychological conditions both for sufferers and families of sufferers. Hypnotherapy is a hypnotic application for therapeutic purposes. Hypnotherapy technique is needed in providing security, calmness, positive thinking and of course can help our loved ones such as family, friends and acquaintances immediately solve the problem. The research design used was quasy experiment (one group pre-posttest design). The population is all Palliative Care patients treated at Yayasan Kanker Indonesia with a total sample of 22 people. Measuring instruments using questionnaires and data analysis using unpaired T-test and Wilcoxon statistical tests to determine whether hypnotherapy can increase family support for patients with palliative care (cancer). The results showed that there was a significant increase in family support for cancer patients after being given hypnotherapy. This can be seen with a significance value or Î± = 0,000 or Î± <0.05.